Bibliometric and literature synthesis on assisted natural regeneration: an evidence base for forest and landscape restoration in the tropics - Oluwajuwon, Tomiwa V.; Chazdon, Robin L.; Ota, Liz; Gregorio, Nestor; Herbohn, John (Frontiers in Forests and Global Change, 2024)
Assisted Natural Regeneration (ANR) is a set of restoration strategies and interventions primarily based on natural regeneration, aimed at accelerating succession and providing multiple benefits in degraded ecosystems and landscapes. These strategies have the potential to significantly contribute to global Forest and Landscape Restoration efforts. However, ANR faces challenges due to limited recognition, support, and formal integration into relevant sectors and restoration policies, particularly in tropical regions. The dearth of evidence-based syntheses further compounds these challenges. To address this gap, a bibliometric analysis of selected scientific publications on ANR (n = 208) from 1987 to 2023 was conducted, using Web of Science and Google Scholar databases. A systematic review was undertaken, using a subset of original research articles (n = 44), to synthesize published data on interventions, contexts, costs, and benefits of ANR and to identify major knowledge gaps. Analysis of bibliometric metadata revealed an increasing annual output of ANR publications in over 80 journals, encompassing various document types and authors from over 40 countries. Despite ANR's formal emergence in the Philippines, Brazil has taken the lead in both its research and implementation, and international collaboration in ANR research has grown. While ANR research focused mostly on ecosystem services and ecological outcomes, social aspects have been poorly studied. Diverse ANR interventions align not only with ecological restoration but also with integrated land management, biodiversity conservation, forest and landscape restoration, and forest management. The cost-effectiveness of ANR implementation, especially in restoration for carbon storage, exhibited considerable variability when compared to active tree planting, and varied with intervention types, time, land use history, and long-term costs. This synthesis provides critical insights and evidence to enhance the effective integration of ANR into restoration and reforestation programs and policies.